A Preliminary Report on Polish–Lebanese Excavations at the St. George's (Mar Girgis) Church in Rachkida (Northern Lebanon). (13th February 2020) - Makowski, Piotr
Abstract : The article discusses the results of limited fieldwork carried out in 2012 at the St. George's (Mar Girgis) church near the village of Rachkida, about 9 km northeast of Batroun. The church, which was probably built by a local Christian community like other villages in the region, was founded on remains from the Byzantine period. As far as could be ascertained, the main body of the building is a three-aisled basilica extended to include a porch on the west side and an additional chapel with two apses at the east end. The church was used in the 12th and 13th centuries and may have kept its sacral function throughout the early Mamluk period, perhaps even later. Throughout its post-ecclesiastical history it functioned as a relatively well-preserved, freestanding roofed building. A large number of diverse finds from the Late Ottoman and French Mandate periods indicate frequent use as a shelter or even a place of temporary habitation. The medieval and post-medieval pottery from the site forms a small but nevertheless significant assemblage, offering unique insight into the local material culture of northern Lebanon. More importantly, it provides a preliminary analysis of several categories of pottery which, to date, have been absent or only cursorily mentioned in archaeological research from Lebanon.